TRENDS AND PROSPECTS OF FORMATION AND FUNCTIONING OF THE FOOD MARKET ON THE EXAMPLE OF GLUTEN-FREE PRODUCTS - PAVLOVA, Olena; SURIAK, Alla; NOVOSAD, Oksana; SHULHACH, Nazariy; KORYTKO, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This study highlights the relevance and importance of gluten-free products, which are responding to consumers' increased interest in dietary restrictions. It examines the health benefits of these products, which open up new perspectives for producers and consumers. The essence of gluten-free foods and their impact on society, including economic and socio-cultural factors, are explored. The growing popularity of these products among people with celiac disease, allergies, and other food restrictions indicates their potential as a lucrative market segment. By analysing the various strategies companies are using to meet consumer needs and address production and marketing challenges, we explore opportunities for growth. The study of international experience provides an overview of key trends and best practices that can be adapted to the Ukrainian context. The domestic market analysis identifies barriers and opportunities for gluten-free product development, considering regional characteristics and demand in Ukraine. The final part of the study discusses forecasts and recommendations for future market development in the country. It identifies potential growth areas, manufacturers' strategies, and critical factors that influence the success of this segment. Overall, the study confirms the importance of developing gluten-free products in the context of healthy eating and opens up opportunities for innovation and growth in this area. Researching the concept of a "gluten-free product" was a vital element of this analytical work, allowing us to examine critical aspects of these products in detail. The definitions and characteristics of gluten-free products have been thoroughly analyzed to understand their nature and importance to consumers. The assessment of the impact of gluten-free products on society included an analysis of their health effects, dietary benefits, and accessibility. The study of international experience in the production of gluten-free products identified best practices and innovative approaches. The domestic market analysis considered consumer demand, the competitive environment, and the potential for development. The study identified key trends and opportunities for Ukrainian gluten-free producers. Particular attention was paid to analyzing the potential for the development of the gluten-free market in the economic and social context. Given the growing interest in healthy lifestyles and dietary restrictions, the analysis highlighted the importance of this food industry sector. The study's findings point to the significant potential of the gluten-free market for development and innovation.
Keywords: gluten-free products; gluten; food restrictions; celiac disease; gluten-free diets; consumer demand; healthy eating